Molecular mechanisms of glial cells in brain disorders following physical exercise - Yan Liu; Shuzhen Ran; Kwok-Fai So; Li Zhang (Stress and Brain, 2023)
Physical exercise generally improves health in humans and animals and may enhance cognitive function and neural function in the brain, especially in the prefrontal cortex and hippocampus. It is also a promising intervention for brain disorders such as psychiatric conditions and neurodegenerative diseases. The neuroprotective mechanisms of exercise are related to synaptic plasticity, neurogenesis, and autophagy. Moreover, the therapeutic effects of exercise are associated with glial cell function in the brain. In this review, we examine the relationship between glial cell function and brain disorders. We also consider the role of glial cells in modulating the effects of exercise on the molecular mechanisms and neural circuits involved in central and peripheral brain function. This review demonstrates that glial cells may play an important role in the effects of physical exercise interventions on the brain, particularly in those with neurological disorders.